Continuous variable entanglement distillation of non-gaussian states - Lassen, Mikael Ostergaard; Dong, Ruifang; Heersink, Joel; Marquardt, Christoph; Filip, Radim; Leuchs, Gerd; Ulrik, L. Andersen (AIP Conference Proceedings, 2009)
We experimentally demonstrate distillation of continuous variable entangled light that has undergone non-Gaussian attenuation loss. The continuous variable entanglement is generated with optical fibers and sent through a lossy channel, where the transmission is varying in time. By employing simple linear optical components, a measurement induced operation and classical communication, we demonstrate that the entanglement is probabilistically increased. © 2009 American Institute of Physics.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Distillation; Entanglement; Quantum information